The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2967/jnumed.116.172627
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT Detects the Location and Extent of Primary Prostate Cancer

Abstract: We evaluated the accuracy of PET/CT with 68 Ga-PSMA-HBED-CC-a 68 Ga-conjugated ligand of human prostate-specific membrane antigen (PSMA)-to localize cancer in the prostate and surrounding tissue at initial diagnosis. Methods: Twenty-one patients with biopsy-proven prostate cancer underwent 68 Ga-PSMA-HBED-CC ( 68 Ga-PSMA) PET/CT at a median of 4 d (range, 0-47 d) before radical prostatectomy. Based on a 6-segment model, the Gleason score and proportion of tumor tissue within each segment (segmental tumor burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
154
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(165 citation statements)
references
References 18 publications
5
154
1
5
Order By: Relevance
“…These studies demonstrated relatively similar results, with a significantly higher 68 Ga-PSMA-11 uptake in positive segments than in negative segments (SUV max of 11.8 vs. 4.9 and 11.0 vs. 2.7, respectively, P , 0.001 each) (50,51). Results from combining 68 Ga-PSMA-11 and multiparametric MRI on 53 preoperative intermediate-/high-risk patients indicated a potential for targeting biopsies.…”
Section: Primary Stagingsupporting
confidence: 66%
See 1 more Smart Citation
“…These studies demonstrated relatively similar results, with a significantly higher 68 Ga-PSMA-11 uptake in positive segments than in negative segments (SUV max of 11.8 vs. 4.9 and 11.0 vs. 2.7, respectively, P , 0.001 each) (50,51). Results from combining 68 Ga-PSMA-11 and multiparametric MRI on 53 preoperative intermediate-/high-risk patients indicated a potential for targeting biopsies.…”
Section: Primary Stagingsupporting
confidence: 66%
“…With regard to intraprostatic tumor localization by 68 Ga-PSMA-11 PET/CT, imaging findings were correlated with histopathology using segment-or voxel-based approaches in several studies (50)(51)(52). These studies demonstrated relatively similar results, with a significantly higher 68 Ga-PSMA-11 uptake in positive segments than in negative segments (SUV max of 11.8 vs. 4.9 and 11.0 vs. 2.7, respectively, P , 0.001 each) (50,51).…”
Section: Primary Stagingmentioning
confidence: 99%
“…Increasing numbers of studies have investigated the potential of 68 Ga-PSMA-11 for intraprostatic tumor localization (97)(98)(99)(100)(101)(102). For example, on the basis of a 6-segment model per slice, histopathologically positive segments (n 5 100 in 21 patients) had significantly higher 68 Ga-PSMA-11 uptake than negative segments (SUV max , 11.8 vs. 4.9), suggesting an SUV max of 6.5 as an optimal discriminator (sensitivity of 67% and specificity of 92% for the detection of tumor-involved segments) (97).…”
Section: Primary Stagingmentioning
confidence: 99%
“…For example, on the basis of a 6-segment model per slice, histopathologically positive segments (n 5 100 in 21 patients) had significantly higher 68 Ga-PSMA-11 uptake than negative segments (SUV max , 11.8 vs. 4.9), suggesting an SUV max of 6.5 as an optimal discriminator (sensitivity of 67% and specificity of 92% for the detection of tumor-involved segments) (97). Other retrospective studies investigating 6 and 9 patients and using segment and voxelwise approaches reported similar results (98,101).…”
Section: Primary Stagingmentioning
confidence: 99%
“…Only 5%-10% of primary PCa lesions have been shown to be PSMA-negative (2), making this class of radiopharmaceutical suitable for diagnosis of primary PCa and for initial staging (3,4). Use for noninvasive tumor grading has also been reported (3).…”
mentioning
confidence: 99%